Environmental Protection and Management - Baldwin, Vivian (Murphy & Moore Publishing, 2022)
The environment is degraded due to various reasons such as population growth, pollution, overconsumption, etc. The practices aimed at conserving and reducing these risks within the environment fall under environmental protection. Environmental management is a dynamic concept which is concerned with the management of environment using different tools and techniques such as environmental accounting, policy, auditing etc. Some of the goals of environmental protection are ensuring sustainable use of resources, conserving biological diversity, controlling land degradation, etc. The primary approaches to environmental protection and management are voluntary and international environmental agreements, and ecosystems approach. This book elucidates new techniques and their applications in a multidisciplinary approach. The topics included herein are of utmost significance and bound to provide incredible insights to readers. For all those who are interested in environmental protection and management, this textbook can prove to be an essential guide.
Keywords: Environmental Engineering